Memikirkan Kembali Kurikulum Literasi Media di Sekolah Dasar - Salman Hasibuan (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The emergence of information and technologies massively brings about changes in society. The later implicate to the increasing use and ownership of the digital media. These changes entangled educational concerns in which elementary age students have been active users of digital media and have more times interact in a connected internet digital manner without cultivated with literacy media curriculum at school in which consequently bearing literacy media divide. Reflected from the phenomenon, it is urged for government to rethinking media literacy curriculum for elementary school. This article intended to overview potentially educational policies of integration literacy media into curriculum. This article used qualitative research with library research approach. The references derive from books, scientific journals, government documents, and research reports. All the data analyzed through processes of data reduction, data display, and drawing conclusion. The results showed that it is urges to integrate literacy media into elementary school curriculum in order to prevent the media literacy divide among students.